Assessment of knowledge, attitude, and practices regarding biomedical waste management among operation room personnel in a tertiary care center - Tejesh C Aanandaswamy (Journal of Anaesthesiology Clinical Pharmacology, 2019)
Background and Aims: Biomedical waste management is an important issue of concern to all healthcare personnel as inappropriate management has the potential for serious infections and noninfectious injury to patients and care providers. Operation room is a department in the hospital wherein large amounts of waste are generated on a daily basis. This study aims to evaluate the knowledge, attitude, and practice regarding biomedical waste among operation room personnel. Material and Methods: This is a cross-sectional study done among various strata of operation room personnel with a questionnaire to evaluate the knowledge, attitude, and practice with respect to biomedical waste management. Results: This study revealed gaps in knowledge and practices among all strata of operation room personnel regarding biomedical waste management. Conclusion: This study highlights the need for appropriate training of all operation room personnel about appropriate waste management practices.